Effect of fiber orientation and elevated temperature on the mechanical properties of unidirectional continuous kenaf reinforced PLA composites - Tharazi Izdihar; Abdul Azam Farah Atiqah; Muhamad Norhamidi; Hui David; Sulong Abu Bakar; Gaff Milan (Reviews on Advanced Materials Science, 2023)
Limitation in practical applications of biopolymer–fiber composite is mainly at higher temperatures. Thus, this study highlights the effects of fiber orientation on the durability of polylactic acid (PLA) reinforced with unidirectional (UD) continuous kenaf fibers at elevated temperatures. PLA and long kenaf fiber were fabricated using the hot-pressing method and stacked at fiber orientations of 0°, 45°, or 90°, relative to the tensile force. Dynamic mechanical analysis of the composites shows excellent anti-shock and temperature-resistant properties of the composite. UD PLA–kenaf composites with a 0° fiber orientation showed an ultimate tensile of ∼190 MPa and a flexural strength of ∼235 MPa, and the strength of the composite was able to retain up to 120°C temperature. The debonding behavior of the fiber from the matrix (fiber pull-out) supported by microscopy proved that interfacial failure occurs from the local strains, which initiate cracking. Interfacial failure and stress transfer have caused a remarkable reduction in composite strength when fibers were oriented at 90°. Hence, this current improvement in the performance of the UD PLA–kenaf fiber composite may potentially replace conventional synthetic fibers, especially for structural automotive applications.